Pendekatan Rekayasa dalam Konservasi Arsitektur Warisan di Taman Sari Yogyakarta - Rahmania Suryaning Widyas; Shofiyyaturrodhiyah M. D. (Journal of Engineering and Applied Technology, 2025)
This study discusses the conservation of the Taman Sari complex in Yogyakarta as an architectural heritage that combines elements of Javanese culture, European influences, and functional principles as a water palace, garden, and defensive fortress, amid challenges of structural degradation, changes in function, and the pressures of urbanization. The research method uses a qualitative-descriptive approach with case studies, examining historical documentation, scientific publications, and digital modeling through Heritage Building Information Modeling (HBIM) and close-range photogrammetry to assess existing conditions, identify critical areas, and formulate engineering-based conservation strategies. The results show that the integration of water elements, building structures, cross-cultural ornaments, and hydraulic systems requires holistic conservation intervention, combining traditional and modern techniques as well as digital documentation to preserve function, aesthetics, and historical value. The conclusion affirms that an engineering conservation approach allows Taman Sari to be fully restored, while supporting educational, cultural, and sustainable tourism experiences.